Factors Affecting the Safety of Shipping of Domestic Ships: Analysis of Human Resources Quality, Infrastructure and Technology - Rachman, Subehana (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Article on Infrastructure, Technology, and Human Resource Quality as They Affect Domestic Ship Navigation Safety. This work aims to develop a hypothesis regarding the relationship between factors that can be applied to subsequent studies. The descriptive qualitative research methodology is applied. The descriptive qualitative approach employs data from online academic media, including digital reference books, Taylor & Francis, Scopus Emerald, Web of Science, DOAJ, EBSCO, and Sinta Journal, as well as from prior research that is pertinent to the current study. This article's conclusions are as follows: 1) Infrastructure Affects Shipping Safety; 2) Technology Affects Shipping Safety; and 3) Human Resource Quality Affects Shipping Safety.